ANALISIS PENGARUH GAYA KEPEMIMPINAN DEMOKRATIS DAN MOTIVASI KERJA TERHADAP DISIPLIN KERJA GURU DI SD NEGERI KECAMATAN KURANJI KOTA PADANG - Usdarisman, Usdarisman; Erpidawati, Erpidawati (UIN Imam Bonjol Padang, 2020)
This study aims to determine how the influence of the principal's democratic leadership style and work motivation on teacher discipline in Elementary Schools (SD) Negeri Padang City. This research uses quantitative methods with correlational research type. The population of this study were all elementary school teachers who were the State Civil Servant (ASN) of Kuranji District, Padang City, totaling 307 people. As a sample, 60 teachers were randomly selected using a lottery system for each population group. The data analysis technique in this research is descriptive and inductive. The data were analyzed statistically using correlation and regression techniques using SPSS version 20. The results showed: 1) The leadership of a democratic school principal contributes to the work discipline of teachers at SD Negeri Kuranji Subdistrict, 2) Work Motivation contributes to the work discipline of teachers at SD Kuranji Subdistrict, Padang City, in this case the better the motivation of teachers, the more discipline the teacher works, 3) The leadership and motivation of democratic school principals contribute to teacher work discipline. Thus, to be able to improve teacher discipline, it is best done through the leadership of a democratic school principal and teacher work motivation.